Development and Evaluation of a Multiplex LAMP Assay for Detecting Mycobacterium tuberculosis in Clinical Samples - P. Gunavathy; B. Usharani; M. Anbazhagi; R. Venkateswari; B. Revathi Mani; M. Muthuraj (Research Perspectives of Microbiology and Biotechnology Vol. 6, 2024)
It is crucial to rapidly and accurately diagnose tuberculosis (TB) to reduce morbidity, mortality, and the risk of transmission. A simple, cost-effective diagnostic test to rapidly detect M. tuberculosis in clinical samples is essential. We evaluated an in-house diagnostic test based on loop-mediated isothermal amplification (LAMP) targeting the M. tuberculosis 16S rRNA gene. It was compared with the Genotype and phenotype assay for diagnosing TB in India. Out of 874 samples processed, the overall sensitivity and diagnostic accuracy were found to be 97.06% (with a confidence interval of 95.69-98.09%) and 97.03% (95.67-98.05%), respectively. The sensitivity and accuracy of the LAMP assay against the GenoType MTBDRplus and MGIT assay were 96.41% (94.61-97.73%) and 98.74% (96.36-99.74%), and 96.38% (94.61-97.69%) and 98.74% (96.38-99.74%), respectively. The kappa values were approximately 0.64 and 0.40 for the genotypic and phenotypic assays. Based on these findings, the LAMP assay could be a suitable point-of-care test for rapid diagnosis of tuberculosis in resource-limited laboratory settings.